Are patient–nurse relationships in breast cancer linked to adult attachment style?. (3rd June 2015) - Harding, Rachel; Beesley, Helen; Holcombe, Christopher; Fisher, Jean; Salmon, Peter
Abstract Aims The aim of this study was to ascertain if patients with breast cancer who have positive attachment models of 'self' and 'other' perceive higher levels of support from nurses than do patients with negative attachment models. Background Attachment models of 'self' and 'other' develop in childhood and affect relationships throughout life. People with negative attachment models tend to perceive themselves as unworthy of receiving support and to perceive others as incapable or unwilling to offer support. Attachment processes are activated when individuals feel threatened and seek support from those close to them. Breast cancer may represent such a threat and relationships between patients with breast cancer and nurses may therefore be influenced by patients' attachment models. Design A between‐subjects cross‐sectional design was used. Explanatory variables were indicators of patients' attachment models. Response variables were patient ratings of nurse support. Covariates were patient age and patient distress levels. Method One hundred and fifty‐three patients with breast cancer, diagnosed 1‐3 years previously, were recruited when attending follow‐up oncology appointments over 51 weeks in 2010–2011. Participants completed questionnaires assessing attachment models, distress and perceived support, from the nurse who was available to support them through their cancer. The hypotheses were tested by logistic regression analysis. Results Patients with more positive models of 'self' perceived more support from nurses. Conclusions Patients' perceptions of nurses when being treated for breast cancer are influenced by patients' own models of attachment. Knowledge of this would help nurses further to individualize the emotional support they give patients.